Visualisation and characterisation of voids in crystalline materials - Turner, Michael J.; McKinnon, Joshua J.; Jayatilaka, Dylan; Spackman, Mark A. (CrystEngComm, 2011)
We present a simple and more realistic alternative to the conventional approach of mapping void space by rolling a probe sphere of variable radius over a fused-sphere representation of a molecular crystal. Based on isosurfaces of the procrystal electron density, this approach can be used to locate and visualise the void space in crystalline materials, as well as readily compute surface areas and volumes of the voids. The method is quite general, computationally rapid, and capable of locating and characterising all "empty" space, and not just the larger cavities and channels, in molecular crystals, organic, metal-organic and inorganic polymers. Examples elaborate on its application to a variety of crystalline systems where voids have been the subject of recent discussion, including porous dipeptides, metal-organic and covalent organic frameworks. Comparison is made with existing computational methods, as well as with the results from experimental techniques that provide estimates of volumes and surface areas of void space and porosity.